PENGUJIAN MODEL DE LONE DAN MC LEAN DALAM PENGEMBANGAN SISTEM INFORMASI IFCA - MEINIE SUSANTY (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of this study was to analyze the positive effect of information quality and system quality on user satisfaction and intensity of system use, user satisfaction positively influences the intensity of the use of the system, the positive influence of user satisfaction and intensity of use of the system to the individual impact, positive influence on the individual impact of organizational impact. This study uses a model of De Lone and Mc Lean (1992) in the development of information systems IFCA in Indonesia. Sample based on the results of the survey questionnaires to managers and supervisors in four of five business units. The results showed that the quality of information has no effect on user satisfaction and system usage intensity. The quality system has positive influence on user satisfaction, but do not affect the intensity of use of the system. User satisfaction has no effect on the intensity of use of the system. Furthermore, the intensity of use of the system has positive influence on individual impact, yet has no effect on user satisfaction of individual impact. The impact of individual positive influence on organizational impact.